The Effect of Self-Efficacy Based Education on the Daily Care of Stroke Patients and its Implications with Counseling - Wiguna, Rizaldi Nanda; Ritarwan, Kiking; Sitohang, Nur Asnah; Sinaga, M. Harwansyah Putra (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
Stroke patients generally experience daily self-care disorders due to old age (elderly), so that motor skills are low. One factor affecting the ability to take care of oneself every day and be motivated to be independent is self-efficacy. The purpose of this study was to analyze the effect of self-efficacy-based education on the daily self-care of stroke patients at the Haji Adam Malik General Hospital and its implications with counselling guidance. The type of research used is a quasi-experimental design using the nonequivalent control group pre- post-test only design method. The population in this study were all ischemic stroke patients at Haji Adam Malik Hospital Medan and a sample of 36 people. Researchers provided educational interventions based on self-efficacy using visual media, discussions, motor skills training, and occupational exercises for three meetings per week with a duration of 30 minutes each session for six weeks. Data collection with primary and secondary data and analyzed by statistical test Paired Sample t-Test. The results showed an effect of self-efficacy-based education on the daily care of stroke patients at Haji Adam Malik Hospital Medan (p-value = 0.000 <0.05) such as motor function and improving their daily activities.